Application of Q [7] solid powder material for selectively removing impurity acetaldehyde and application of Q [7] solid powder material
Through the selective adsorption and desorption technology of Qiyuan Guahuan Q[7] solid powder material, the high energy consumption and high cost of acetaldehyde removal in vinyl acetate are solved, and a low-energy-consuming and efficient separation process is achieved, and the improvement of the high energy consumption and high efficiency separation process is achieved. The application range and adsorption efficiency of the material are obtained.
Patent Information
- Application Number
- CN202311356849.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2023-10-19
- Publication Date
- 2025-01-14
AI Technical Summary
The method of removing impurity acetaldehyde from vinyl acetate in the prior art has problems such as high energy consumption, high equipment requirements and high production costs. The existing materials have low polarity and poor water solubility, which limits their application scope.
The seven-member melon ring Q[7] solid powder material selectively adsorbs acetaldehyde in vinyl acetate, and adsorbs acetaldehyde through its cavity, port and outer wall to achieve a low-energy consumption and efficient separation process, and desorption by heating Recycle materials for recycling.
The separation process is simplified, energy consumption is reduced, and production costs is reduced. The material has good water solubility, large polarity, wide application range, excellent adsorption efficiency and stable separation effect.
Smart Images

Figure CN119306603A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical engineering technology, and in particular to a method for removing acetaldehyde as an impurity from vinyl acetate. In particular, the method uses a seven-membered cucurbitacin Q[7] solid powder material to adsorb acetaldehyde in vinyl acetate, which has low energy consumption and simple process. Background Art
[0002] Vinyl acetate (VAc) is a colorless, transparent liquid with a strong odor. It is one of the 50 largest chemical raw materials in the world. As an important organic chemical raw material, it is mainly used to produce derivatives such as polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), vinyl chloride-vinyl acetate copolymer (EVC), and polyacrylonitrile comonomer. These derivatives are widely used in chemical products such as coatings, slurries, adhesives, vinylon, films, vinyl copolymer resins, and acetal resins. Therefore, the purity of vinyl acetate directly affects the quality of these derivatives. Vinyl acetate produced from the existing synthesis process contains unreacted raw materials and by-products, so vinyl acetate needs to be further purified.
[0003] Acetaldehyde, also known as acetic acid aldehyde, is an organic compound with the chemical formula CH3CHO. It is a colorless transparent liquid, soluble in water, and miscible in ethanol, ether, benzene, gasoline, toluene, xylene, etc. It is mainly used as a reducing agent, bactericide and for preparing standard solutions when determining aldehydes by colorimetry. It is used in industry to manufacture polyacetaldehyde, acetic acid, synthetic rubber, etc. Acetaldehyde is a by-product in the production of vinyl acetate. In order to obtain high-purity vinyl acetate, acetaldehyde needs to be removed.
[0004] At present, the separation methods for vinyl acetate and acetaldehyde are gas phase oxidation and distillation. The separation technology of vinyl acetate units in these routes has the problems of complex separation process, large investment and high energy consumption for the mixture of vinyl acetate and acetaldehyde, methyl acetate, acrolein, etc.
[0005] In the traditional separation technology of vinyl acetate unit in gas phase oxidation process, the feed of the second distillation tower includes the mixed component material from the top of the first distillation tower in the separation process, the reflux material of the fourth distillation tower and the mixed component material from the top of the fifth distillation tower. After the fuzzy cutting separation of vinyl acetate and light and heavy components in the second distillation tower, part of vinyl acetate, most of methyl acetate, and all light components, including acrolein, acetaldehyde, water, oxygen, nitrogen and ethylene are separated from the top of the tower from the mixed components. After the top gas of the second distillation tower is condensed, a small amount of non-condensable gas is discharged to the upstream reaction process for recovery. A distillation tank is set after the top condenser of the second distillation tower, and the top condensate is layered in the distillation tank. The lower layer of the distillation tank is mainly water and is sent to the downstream for treatment; part of the upper layer of the distillation tank is used as the reflux of the second distillation tower, and the other part is used as the top discharge of the second distillation tower to remove acetaldehyde from the fourth distillation tower. The components after acetaldehyde removal are returned from the fourth distillation tower and used as feed for the second distillation tower for cyclic separation. The bottom discharge of the second distillation tower does not contain light components such as acrolein and acetaldehyde, and only contains vinyl acetate, ethyl acetate and trace amounts of methyl acetate. For this component in the bottom of the second distillation tower, a third distillation tower is usually set up for subsequent separation. The third distillation tower is responsible for purifying the vinyl acetate in the incoming material so that the vinyl acetate output from the top of the tower reaches the product purity requirement of 99.86%. The bottom discharge of the third distillation tower mainly contains vinyl acetate and ethyl acetate, which are usually sent to downstream devices such as polyvinyl alcohol devices for treatment, or a separate processing unit can be set up to recover the vinyl acetate therein.
[0006] Chinese patent CN103030537 discloses a method for distilling acetaldehyde in a vinyl acetate production process by acetylene, which can inhibit the self-polymerization of acetaldehyde in the distillation process of acetaldehyde in the production process of vinyl acetate by acetylene. Specifically, in the process of preparing vinyl acetate by acetylene, when zinc acetate / activated carbon is used as a catalyst and acetic acid and acetylene are used as raw materials to synthesize vinyl acetate (VAC), a by-product acetaldehyde is generated, especially in the catalyst activation period, the amount of acetaldehyde generated is more. The crude vinyl acetate produced by its synthesis is degassed, roughly distilled, and distilled to obtain a vinyl acetate product. Among them, the light components separated by the roughly distillation are extracted, and the organic term is returned to the system to recover vinyl acetate. The aqueous phase containing acetaldehyde, acetone, vinyl acetate and other substances enters the acetaldehyde distillation tower to refine the by-product acetaldehyde. The product acetaldehyde can be distilled from the top of the distillation tower, and acetone and a small amount of vinyl acetate are recovered in the middle side line. During the process, during the catalyst activation period, paraldehyde is produced in the acetaldehyde distillation tower. The generation cycle is generally about 7 to 10 days, and some impurities carried by the catalyst carrier also enter the system during the activation period. The paraldehyde generated by acetaldehyde self-polymerization causes a high amount of paraldehyde in the acetaldehyde distillation tower, and the VAC produced in the middle cannot be recovered, which affects the quality of the product refined VAC. Therefore, it has a great impact on the entire system. It not only affects the stability of production, but also directly affects the quality of refined vinyl acetate products and by-product acetaldehyde. In severe cases, it will also bring safety hazards to the transportation of by-product acetaldehyde.
[0007] Chinese patent CN 104030921 B discloses a method for separating vinyl acetate. The patent adopts the dividing wall distillation technology to replace the original distillation technology, and the separation effect can reach or exceed the purity of the original process, and the total energy consumption is reduced by 15-35%, which saves energy consumption and equipment investment to a certain extent.
[0008] Chinese patent CN 107011172 A discloses the use of a dividing wall tower to purify vinyl acetate, further optimizing the refining process and reducing process energy consumption.
[0009] Chinese patent CN115894237A discloses a method for separating and purifying vinyl acetate, using cucurbituril [6] channel type crystal material as adsorbent to selectively adsorb acetaldehyde in a vinyl acetate mixed solution to achieve separation and purification of vinyl acetate; the separation process of the present invention is simple to operate, has low equipment requirements, and has excellent separation effect; the separation process does not require distillation operation, has low energy consumption, saves energy, and has low purification cost; the used materials are highly stable and can be regenerated and reused. However, cucurbituril [6] has the following disadvantages: its polarity is low and its water solubility is poor, which limits its wide application; in addition, the method uses cucurbituril [6] channel type crystal material, and the crystal material is obtained by recrystallization of powder, and the preparation process is relatively complicated, which makes the production cost of this solution relatively high.
[0010] In view of the many deficiencies in the prior art of removing acetaldehyde as an impurity from vinyl acetate, the present invention provides a method for removing acetaldehyde as an impurity from vinyl acetate, which utilizes a seven-membered cucurbitacin Q[7] solid powder material to adsorb acetaldehyde in vinyl acetate, has low energy consumption and a simple process. Summary of the invention
[0011] In view of the shortcomings in the art, the present invention provides a method for removing acetaldehyde as an impurity from vinyl acetate, using a seven-membered cucurbitacin Q[7] solid powder material to adsorb acetaldehyde in vinyl acetate, which has low energy consumption and a simple process.
[0012] The present invention provides the use of Q[7] solid powder material for selectively removing impurity acetaldehyde, wherein the structural formula of Q[7] solid powder material is.
[0013]
[0014] Preferably, the outer diameter of the Q[7] solid powder material is The cavity diameter is Port diameter is
[0015] The present invention also provides a method for removing impurity acetaldehyde from vinyl acetate by using Q[7] solid powder material to selectively remove impurity acetaldehyde, wherein the molar ratio of the Q[7] solid powder material to the impurity acetaldehyde in the vinyl acetate is approximately (1-1.5):1.
[0016] Preferably, the Q[7] solid powder material can be desorbed, regenerated and reused after selectively adsorbing acetaldehyde.
[0017] Preferably, the Q[7] solid powder material can be desorbed and regenerated for reuse after selectively adsorbing acetaldehyde, and the desorption and regeneration temperature is 80-100°C.
[0018] Preferably, a method for removing impurity acetaldehyde from vinyl acetate using Q[7] solid powder material for selectively removing impurity acetaldehyde is provided, wherein the temperature for selectively removing impurity acetaldehyde from the vinyl acetate is 10-25°C, preferably 20°C.
[0019] Preferably, a method for removing impurity acetaldehyde from vinyl acetate by using Q[7] solid powder material to selectively remove impurity acetaldehyde, wherein the vinyl acetate is a mixture of vinyl acetate containing acetaldehyde.
[0020] Preferably, the mixture of vinyl acetate containing acetaldehyde may be a crude product of vinyl acetate containing impurities obtained in large-scale industrial production.
[0021] In addition, the present invention provides a method for selectively removing acetaldehyde impurity from vinyl acetate using Q[7] solid powder material, and its application in removing acetaldehyde impurity from vinyl acetate in the industrial production of vinyl acetate.
[0022] Compared with the prior art, the present invention has the following main advantages: (1) the separation process is simple to operate and has low equipment requirements; (2) the separation process does not require distillation operation, has low energy consumption, saves energy, and reduces the production cost of acetaldehyde and vinyl acetate; (3) Q[7] has the advantages of good water solubility, high polarity, good selectivity, etc., and has a wide range of applications; at the same time, Q[7] has a large cavity and can contain a large number of objects over a wide range; (4) the present invention uses Q[7] solid powder material, which further reduces the cost compared to the crystal material used in the prior art; at the same time, the powder can adsorb acetaldehyde through multiple channels such as the cavity, port and outer wall of its molecules, and has a better adsorption efficiency than the crystal; (5) the Q[7] solid powder material used is highly stable and can be recycled without reducing the separation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a GC characterization result diagram of vinyl acetate without impurities in Example 1;
[0024] Figure 2 This is a GC characterization result diagram of the adsorption of acetaldehyde from vinyl acetate containing acetaldehyde as an impurity by the Q[7] solid powder material of Example 2;
[0025] Figure 3 The Q[7] solid powder material of Example 3 after desorption 1 H NMR characterization results. DETAILED DESCRIPTION
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.
[0027] Q[7] Solid powder material
[0028] Cucurbituril (also known as cucurbituril, Q[n]s or CB[n]s for short) is a highly symmetrical cage compound composed of 2n methylene bridged n glycoside urea units. The overall appearance is similar to pumpkin, and the main monomer glycoside urea is similar to gourd. Pumpkin and gourd belong to the same family of Cucurbitaceae (Latin: cucurbia), and urea is used as a raw material in the synthesis process, so it was finally named cucurbituril. The study of Q[n]s can be traced back to 1905, when German chemist Behrend and others used glycoside urea and polyformaldehyde as raw materials to synthesize a white solid that is neither soluble in water nor in organic solvents in an inorganic acid medium. At the same time, they found that the substance can form crystals with Congo red, KMnO4, AgNO3 and other substances. Due to the limitations of the test characterization technology at the time, its composition and structure were not clear, so it did not attract people's attention. With the gradual rise of supramolecular chemistry and the improvement of detection methods, Freeman, Mock and others re-studied the synthesis of the white solid, and obtained complex crystals after coordinating it with calcium ions in a sulfuric acid solution. In 1981, they determined the exact structure of the first member of the cucurbitacin family, the six-membered cucurbitacin (Q[6]), by X-ray single crystal diffraction technology. After the discovery of Q[6], Korean scholar Kim and Australian scholar Day and others discovered several other new homologues of the cucurbitacin family by changing the reaction conditions, namely the five-membered cucurbitacin, the seven-membered cucurbitacin and the eight-membered cucurbitacin (Q[5], Q[7] and Q[8]).
[0029] The structural data and schematic diagram of the Q[7] solid powder material of the present invention are as follows:
[0030]
[0031]
[0032] In addition, Q[7] solid powder material has some homologues, such as Q[5], Q[6], and Q[8]. Their structural parameters are as follows:
[0033]
[0034] Crude vinyl acetate containing impurities
[0035] The crude product of vinyl acetate containing impurities of the present invention is a mixture of vinyl acetate containing acetaldehyde and can be obtained in large-scale industrial production.
[0036] Method for removing acetaldehyde impurity from vinyl acetate using caged compounds
[0037] The method for removing acetaldehyde impurity from vinyl acetate using a caged compound of the present invention is a method for removing acetaldehyde impurity from vinyl acetate using a caged compound, such as Q[7] solid powder, wherein the vinyl acetate is a mixture containing vinyl acetate and acetaldehyde.
[0038] Due to the difference in molecular structure between acetaldehyde and vinyl acetate, the Q[7] solid powder material in the separation method can form a host-guest complex with acetaldehyde. The host-guest complex is unstable and will gradually decomplex when heated to above 60°C, releasing the adsorbed acetaldehyde. After the desorption process is completed, the Q[7] solid powder material can be reused without a decrease in selectivity.
[0039] The Q[7] solid powder material can be obtained by filtering and removing acid after the reaction of glycoside urea and polyformaldehyde, and can be directly used to remove the impurity acetaldehyde from vinyl acetate after drying.
[0040] The adsorption time of the adsorption method changes with the changes of factors such as the sample amount, the adsorption temperature and the ratio of acetaldehyde in vinyl acetate.
[0041] Preferably, the adsorption method uses Q[7] solid powder material to selectively adsorb acetaldehyde in vinyl acetate containing acetaldehyde, and after removing acetaldehyde from vinyl acetate, the Q[7] solid powder material is air-dried at room temperature to remove the mixture adsorbed on the surface, and finally desorbed to obtain a reusable Q[7] solid powder material.
[0042] The time for air-drying the Q[7] solid powder material at room temperature to remove the mixture adsorbed on the surface can be adjusted according to the sample amount. Under the condition of less than 20°C, the host-guest complex still exists stably, while the mixture of acetaldehyde and vinyl acetate adsorbed on the surface can be gradually removed. By removing the mixture adsorbed on the surface, the purity of the acetaldehyde separated by adsorption is improved.
[0043] The acetaldehyde molecules adsorbed in the Q[7] solid powder material can be desorbed by heating, preferably at a temperature of 80 to 100° C., and the desorption time can be adjusted according to the sample amount. At this temperature, the host-guest complex is unstable, and the adsorbed acetaldehyde molecules will gradually be released, while the Q[7] solid powder material is stable. After desorption, the Q[7] solid powder material can continue to be used to remove impurity acetaldehyde from vinyl acetate for the next cycle.
[0044] As used herein, the term "about" refers to an amount, level, value, dimension, size, or amount that differs by up to 30%, 20%, or 10% compared to the amount, level, value, dimension, size, or amount of a reference product. Percentages used herein, unless otherwise indicated, are by weight.
[0045] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.
[0046] Experimental Materials:
[0047]
[0048] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0049] When the molar ratio of Q[7] solid powder material to acetaldehyde impurity in vinyl acetate is about (1-1.5):1, the adsorption method of the present invention is applicable.
[0050] Test Example 1: GC Detection
[0051] Test sample: high purity, impurity-free vinyl acetate
[0052] Related information of experimental equipment for GC detection: GC-2014 Shimadzu gas chromatograph, origin: Japan.
[0053] Detection experimental steps:
[0054] 1. Check the plug and connection lines to see if they are connected properly; check the air pipe connection and whether the liquid level of the hydrogen generator is within the allowable working range.
[0055] 2. Open the valve of the carrier gas (N2) cylinder, the fuel gas (H2) generator, and the power supply of the auxiliary fuel gas (compressed air) generator.
[0056] 3. Rotate the pressure reducing adjusting screw to make the secondary pressure gauge indicate the required pressure. The carrier gas is about 0.7Mpa, and the fuel gas and auxiliary gas are 0.3Mpa.
[0057] 4. Turn on the main power switch of the host. The touch screen display of the host is in self-checking and the blower motor in the column chamber is running.
[0058] 5. Turn on the computer connected to the gas chromatograph and run the gas chromatograph working software.
[0059] 6. After the software is successfully connected to the instrument, set the split ratio to 50, SPL1 temperature to 250℃, SFID1 temperature to 280℃, column oven temperature to 50℃, and running time to 25min on the control panel.
[0060] 7. After setting the parameters according to the specified analysis method, run the system and the temperature of each zone will begin to rise toward the set value. When the temperature reaches the set value, the READY light will turn on and the ignition will start.
[0061] 8. Check whether the instrument baseline is stable. Once the baseline is straight, you can run a single injection test and use a 10u injection needle to inject 1ul of sample from the injection port.
[0062] 9. After the test, click "Shut down system" on the work button, and then restore the detector, injection port, and column temperature settings to room temperature. When the temperature of the chromatographic column and injection port drops below 100°C, turn off the chromatograph power switch and computer power in turn, and finally turn off the hydrogen generator, air generator power, and nitrogen cylinder main valve.
[0063] Peak table
[0064] SFID1
[0065]
[0066] The peak time of vinyl acetate is 2.471. The peak height represents the signal value output by the detector when vinyl acetate elutes from the column at the maximum concentration. The peak area refers to the integral value of the vinyl acetate peak height and the retention time of vinyl acetate.
[0067] Example 1: Adsorption of acetaldehyde in vinyl acetate by Q[7] solid powder material
[0068] At room temperature and pressure, take a 20mL culture bottle, add 5mL of vinyl acetate containing acetaldehyde (vinyl acetate content is 98.72%, acetaldehyde content is 0.37%), take 0.5g Q[7] solid powder material and place it in the culture bottle, seal it, place it at 20℃ for 48 hours, and then air-dry the obtained powder.
[0069] After the adsorption is completed, the remaining vinyl acetate in the culture bottle can be measured by gas chromatography to detect whether there is any acetaldehyde residue in the vinyl acetate.
[0070] Test Example 2: GC Detection
[0071] Test sample: Powder obtained in Example 1
[0072] Related information of experimental equipment for GC detection: GC-2014 Shimadzu gas chromatograph, origin: Japan.
[0073] Detection experimental steps:
[0074] 1. Check the plug and connection lines to see if they are connected properly; check the air pipe connection and whether the liquid level of the hydrogen generator is within the allowable working range.
[0075] 2. Open the valve of the carrier gas (N2) cylinder, the fuel gas (H2) generator, and the power supply of the auxiliary fuel gas (compressed air) generator.
[0076] 3. Rotate the pressure reducing adjusting screw to make the secondary pressure gauge indicate the required pressure. The carrier gas is about 0.7Mpa, and the fuel gas and auxiliary gas are 0.3Mpa.
[0077] 4. Turn on the main power switch of the host. The touch screen display of the host is in self-checking and the blower motor in the column chamber is running.
[0078] 5. Turn on the computer connected to the gas chromatograph and run the gas chromatograph working software.
[0079] 6. After the software is successfully connected to the instrument, set the split ratio to 50, SPL1 temperature to 250℃, SFID1 temperature to 280℃, column oven temperature to 50℃, and running time to 25min on the control panel.
[0080] 7. After setting the parameters according to the specified analysis method, run the system and the temperature of each zone will begin to rise toward the set value. When the temperature reaches the set value, the READY light will turn on and the ignition will start.
[0081] 8. Check whether the instrument baseline is stable. Once the baseline is straight, you can run a single injection test and use a 10u injection needle to inject 1ul of sample from the injection port.
[0082] 9. After the test, click "Shut down system" on the work button, and then restore the detector, injection port, and column temperature settings to room temperature. When the temperature of the chromatographic column and injection port drops below 100°C, turn off the chromatograph power switch and computer power in turn, and finally turn off the hydrogen generator, air generator power, and nitrogen cylinder main valve.
[0083] Peak table
[0084] SFID1
[0085]
[0086] Figure 2 Peak 1 in the figure is the information related to the elution peak of acetaldehyde, and peak 2 is the information related to the elution peak of vinyl acetate. As can be seen from the figure, the adsorption efficiency of Q[7] on acetaldehyde reaches 97.839%.
[0087] Example 2: Regeneration of Q[7] solid powder material
[0088] 0.5 g of the Q[7] solid powder material subjected to supersaturated adsorption of acetaldehyde in Example 1 was heated in a vacuum oven at 100° C. for 2 hours. The sample was designated as Q[7]-D and kept for later use.
[0089] Test Example 3: 1H NMR detection
[0090] Test sample: Regenerated powder Q[7]-D obtained in Example 2
[0091] Instrument related information: JNM ESC400M nuclear magnetic resonance spectrometer, single-phase 220v 50Hz3Kw.
[0092] Experimental steps and main parameters:
[0093] 1. Double-click the DELTA icon on the computer desktop to enter the NMR spectrometer operating software system, connect the spectrometer and the magnet, and enter the user name Delta and password Delta to log in to the spectrometer control interface.
[0094] 2. Add a sample menu item in the Sample tab, create a sample name, select D2O as the deuterated reagent and put it into the corresponding sample slot code. After confirming that it is correct, create the determination (Job title) corresponding to the sample in the lower right corner of the Sample tab.
[0095] 3. Select Hydrogen Spectrum under Job title, set the number of scans to 32 times in the experimental parameter interface, and after confirmation, click Submit Job in the lower right corner.
[0096] 4. After the experiment is completed, the operator should lock the sample and stop rotating the NMR tube, click the button (Eject), take the NMR tube out of the magnet and place it on the automatic sampler, and finally process the data results of the sample.
[0097] Q[7]-D, 1 H NMR(400MHz,D2O,298K,ppm)δ16.00(d,12H),5.53(s,12H),16.00(d,12H)
[0098] exist 1 In the H NMR spectrum, it was found that the signal of the hydrogen atom corresponding to acetaldehyde had disappeared, which indicated that the Q[7] solid powder material had completed desorption and regeneration and all acetaldehyde molecules had been released.
[0099] Examples 3, 5, 7: Adsorption of acetaldehyde in vinyl acetate by Q[7] solid powder material Comparative Example 1: Adsorption of acetaldehyde in vinyl acetate by Q[6] solid powder material
[0100] The steps of Examples 3, 5, 7 and Comparative Example 1 are substantially the same as those of Example 1, except for the amount of Q[7] / Q[6] and the temperature for selectively removing acetaldehyde impurity from the vinyl acetate, as shown in the following table:
[0101]
[0102]
[0103] Examples 4, 6, 8: Regeneration of Q[7] solid powder material
[0104] Comparative Example 2: Regeneration of Q[6] solid powder material
[0105] Examples 4, 6, 8 and Comparative Example 2 correspond to Examples 3, 5, 7 and Comparative Example 1, respectively, and the steps are basically the same as those of Example 2, except for the temperature of the vacuum oven, as shown in the following table:
[0106] Serial number Vacuum oven temperature Example 2 100℃(Q[7]) Example 4 80℃(Q[7]) Example 6 90℃(Q[7]) Example 8 100℃(Q[7]) Comparative Example 2 100℃(Q[6])
[0107] After testing, the experimental effects of Examples 3, 5, and 7 are equivalent to those of Example 1, and the experimental effects of Examples 4, 6, and 8 are equivalent to those of Example 2.
[0108] In summary, it can be seen that the use of the Q[7] solid powder material provided by the present invention to selectively remove the impurity acetaldehyde and its application and method have simple operation in the separation process and low equipment requirements; the separation process does not require distillation operation, has low energy consumption, saves energy, and reduces the production cost of acetaldehyde and vinyl acetate; the Q[7] solid powder material used has high stability and can be recycled, and the separation effect will not be reduced. Further, the technical effect of Q[7] is more advantageous than that of Q[6]: first, Q[7] has good water solubility, high polarity, good selectivity and other advantages, and has a wide range of applications; at the same time, Q[7] has a large cavity, and can contain a large number of objects over a wide range; further, the present invention uses Q[7] solid powder material, which further reduces the cost compared to the crystal material used in the prior art; at the same time, the powder can adsorb acetaldehyde through its molecular cavity, port and outer wall, and has a better adsorption efficiency than the crystal.
[0109] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. Use of Q[7] solid powder material for selectively removing impurity acetaldehyde, wherein the structural formula of Q[7] solid powder material is:
2. The use according to claim 1, characterized in that The outer diameter of the Q[7] solid powder material is The cavity diameter is Port diameter is 3. A method for removing acetaldehyde impurity from vinyl acetate using the use as claimed in claim 1, characterized in that: The molar ratio of the Q[7] solid powder material to the impurity acetaldehyde in the vinyl acetate is (1-1.5):
1.
4. The method according to claim 3, characterized in that The vinyl acetate is a mixture of vinyl acetate containing acetaldehyde.
5. The method according to claim 4, characterized in that The vinyl acetate mixture containing acetaldehyde is a crude product of vinyl acetate containing impurities obtained in large-scale industrial production.
6. The method according to claim 3, characterized in that The impurity acetaldehyde can be selectively removed from the vinyl acetate.
7. The method according to claim 6, characterized in that The temperature for selectively removing acetaldehyde impurity from the vinyl acetate is 10-25°C.
8. The method according to claim 7, characterized in that The temperature for selectively removing acetaldehyde as an impurity from the vinyl acetate is 20°C.
9. The method according to claim 3, characterized in that: After selectively adsorbing acetaldehyde, the Q[7] solid powder can be desorbed, regenerated and reused.
10. The method according to claim 9, characterized in that The desorption regeneration temperature is 80-100°C.
11. Use of the method according to any one of claims 3 to 10 in removing impurity acetaldehyde in the industrial production of vinyl acetate.
Citation Information
Patent Citations
Method for separating vinyl acetate
CN104030921B
Method and device for refining vinyl acetate by using partition tower
CN107011172A
Vinyl acetate separation and purification method
CN115894237A